Comparison of fatty acid composition, phytochemical profile and antioxidant activity in four flax (Linum usitatissimum L.) varieties - Qiu, Caisheng; Wang, Hong; Guo, Yuan; Long, Songhua; Wang, Yufu; Abbasi, Arshad Mehmood; Guo, Xinbo; Jarvis, Devra I. (Elsevier, 2020)
The present study evaluates variations among flaxseed varities in terms of fatty acid composition, phytochemical profile, and antioxidant activity determined by oxygen radical absorbance capacity (ORAC), 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and ferrous ion reducing antioxidant power (FRAP) assays. Significant variations in fatty acid composition, phenolic acids and lignan were observed in flaxseed varieties from different countries. Among them, unsaturated fatty acids accounted over 4/5 of total fatty acid content. The highest ratio of linolenic acid of total fatty acid was observed in USPEA, whereas the lowest one was found in Yexiao. USPEA showed the highest content of total phenolics, as well as flaxseed lignan. In general, total phenolics appeared to be the main contributors of antioxidant capacity of flaxseed, which presented significant positive correlation. Our study revealed that both cultivar and origin of seed significantly affected fatty acid composition, phenolic acids, lignans and subsequent antioxidant activity of flaxseed. These results provided new aspects of breeding resources of flaxseed cultivars by presenting their quality specification and possible commercial value.